Groundwater flow pattern and water level fluctuation in western parts of Chitwan valley (Journal of Nepal Geological Society, 2016)
Study of flow pattern and water level fluctuation in the western part of the Chitwan Valley was carried out in the area of 274.48 km2. The study area consists of alluvial deposits of the Narayani and the Rapti River of Pleistocene to Recent age. Aquifers in the study area are unconfined and semi confined to confined types. Based on the static water level, Jagatpur, Sukranagar and Gunjanagar are deep tube well zone and Shivanagar, Parbatipur, Patihani, Gitanagar are shallow tube well zone. The western half area discharges groundwater to the Narayani River and southern half discharges to the Rapti River rather than getting recharged throughout the year. Average water level fluctuation is 2.34 m with high fluctuation of 4.88 m at Sukranagar and low 0.49 m at Dibyanagar VDC. This fluctuation is directly related to rainfall.